The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/cncr.33861
|View full text |Cite
|
Sign up to set email alerts
|

Individual‐ and neighborhood‐level socioeconomic status and risk of aggressive breast cancer subtypes in a pooled cohort of women from Kaiser Permanente Northern California

Abstract: BACKGROUND: Low socioeconomic status (SES) has been associated with a higher risk of aggressive breast cancer (BC) subtypes, but few studies have examined the independent effects of both neighborhood-level socioeconomic status (nSES) and individual-level SES measures. METHODS: This study included 5547 women from the Pathways and Life After Cancer Epidemiology cohorts who were diagnosed with invasive BC. Generalized estimating equation models were used to examine associations of nSES (a composite score based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Mechanisms purported to explain the association of SES with BC aetiology, particularly BC subtypes, include reproductive and environmental factors and chronic stress [ 37 , 38 ]. An increasing number of women, particularly high SES women, who entered the workforce over the last decades, have delayed childbearing, lower parity and higher use of hormonal contraceptives compared to women of lower SES [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms purported to explain the association of SES with BC aetiology, particularly BC subtypes, include reproductive and environmental factors and chronic stress [ 37 , 38 ]. An increasing number of women, particularly high SES women, who entered the workforce over the last decades, have delayed childbearing, lower parity and higher use of hormonal contraceptives compared to women of lower SES [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms purported to explain the association of SES with BC aetiology, particularly BC subtypes, include reproductive and environmental factors and chronic stress [ 37 , 38 ]. An increasing number of women, particularly high SES women, who entered the workforce over the last decades, have delayed childbearing, lower parity and higher use of hormonal contraceptives compared to women of lower SES [ 38 ]. The increased prevalence of these risk factors mainly among women of greater educational attainment contribute to their higher incidence, particularly of tumours with positive hormone receptors, the more common and less aggressive subtype of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Time to surgery might matter very little for indolent, screen-detected cancers, but time to treatment start might matter very much for fast-growing, interval cancers . These faster-growing cancers are more common in certain patient populations with an association seen between worse socioeconomic status and nonluminal A tumors . We wonder if including these socioeconomic indicators in the overall model would mitigate the association between time to surgery and survival seen in this study.…”
mentioning
confidence: 99%
“…Contextual factors that encompass societal conditions and policy decisions, neighborhood disadvantage, and individual socioeconomic deprivation all contribute to the racial disparity in breast cancer mortality . Emerging evidence indicates that social determinants can also influence tumor biology …”
Section: Introductionmentioning
confidence: 99%
“…8,[18][19][20][21][22] Emerging evidence indicates that social determinants can also influence tumor biology. 14,15,23,24 The Oncotype DX 21-gene Breast Recurrence Score (RS) is the most commonly ordered genomic biomarker for breast cancer in the US, 25 and guidelines for systemic adjuvant therapy are based on this gene expression profile for patients with ER-positive, axillary node-negative tumors. 26 In a previously reported analysis of the the Surveillance, Epidemiology, and End Results (SEER) Oncotype Dx Database, 12 we demonstrated that ER-positive, axillary node-negative breast cancer tumors diagnosed in Black women were 30% more likely to have a high-risk RS compared with tumors from White women.…”
mentioning
confidence: 99%